2015
DOI: 10.1073/pnas.1500877112
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in brain alters dopamine turnover and causes behavioral disorders

Abstract: Diabetes and insulin resistance are associated with altered brain imaging, depression, and increased rates of age-related cognitive impairment. Here we demonstrate that mice with a brain-specific knockout of the insulin receptor (NIRKO mice) exhibit brain mitochondrial dysfunction with reduced mitochondrial oxidative activity, increased levels of reactive oxygen species, and increased levels of lipid and protein oxidation in the striatum and nucleus accumbens. NIRKO mice also exhibit increased levels of monoam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
249
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(274 citation statements)
references
References 65 publications
3
249
0
5
Order By: Relevance
“…Mood and metabolic disorders are frequent co-morbidities, [41,42] with overlapping pathophysiology (eg inflammation, insulin resistance, neurocognitive deficits), and animal studies link central insulin resistance to behavioural changes. [43] It should be considered if the effects of shiftwork on mental health might contribute to the increased metabolic disease already associated with these work schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Mood and metabolic disorders are frequent co-morbidities, [41,42] with overlapping pathophysiology (eg inflammation, insulin resistance, neurocognitive deficits), and animal studies link central insulin resistance to behavioural changes. [43] It should be considered if the effects of shiftwork on mental health might contribute to the increased metabolic disease already associated with these work schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, changes in insulin signalling in different models of rodents led to memory impairments [55, 123] and other age-related cognitive alterations [124]. Noteworthy, paradoxically, deletion of IRS-2 in AD mouse model has previously been shown to reduce amyloid deposition and to rescue behavioral deficits [54].…”
Section: Brain Insulin Resistance In Ad and Tauopathies: Cause Or Conmentioning
confidence: 99%
“…A recent study provided an important advance in this field by showing that specific deletion of brain insulin receptors in mice (NIRKO mice) led to augmented anxiety and depressive-like behavior (9). NIRKO mice further presented brain alterations in mitochondrial morphology and function, elevated oxidative stress, and decreased dopamine signaling (9).…”
mentioning
confidence: 99%
“…NIRKO mice further presented brain alterations in mitochondrial morphology and function, elevated oxidative stress, and decreased dopamine signaling (9). While an early study found that NIRKO mice do not show major learning and memory impairment (10), the study by Kleinridders et al (9) demonstrated that deletion of insulin receptors led to important defects in brain function.…”
mentioning
confidence: 99%